Fictional male bodies and their affective power in the Northern Irish plays My Name, Shall I Tell You My Name? and The Belle of the Belfast City by Christina Reid - Cordova, Marcos Neto de (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2022.